A method to predict change propagation within building information model - Saoud, Lama Adel; Omran, Jamal; Hassan, Bassam; Vilutienė, Tatjana; Kiaulakis, Arvydas (Journal of Civil Engineering and Management, 2017)
This study examines problem of the management of design changes caused by the complexity of the design process and the lack of knowledge of all aspects of the design dependencies. This paper addresses the subject of design changes management in the context of a multidisciplinary collaborative environment of Building Information Modelling (BIM). Due to evolving role of BIM in designing of building projects and the increasing complexity of the design process a need to develop change management based on BIM methodology aroused. The application of BIM to construction projects has the potential to enhance the quality of information provided for making critical design decisions. Trusted change propagation is the key for successful change management. Paper describes developed method to predict the propagation of change through the building information model and provides the concept of visual technology to help designers to predict the change in the construction industry. The developed method includes the use of parameter-based Design Structure Matrix (DSM) as a tool for predicting change propagation. The novelty of research is the proposed integration of DSM with BIM to support the visual representation of predicting change within BIM. Case study demonstrates the possibilities of method in BIM environment.